E. Jerome O'Connor papers - O'Connor, E. Jerome, 1891-1977.
Correspondence, logbook, resume, newspaper clippings, and other papers pertaining primarily to O'Connor's career as an architect in the Washington, D.C., area.
Library of Congress Prints and Photographs Division.
Architect of Washington, D.C.; coordinating architect for the Pentagon in Arlington, Virginia.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Architecture -- Washington (D.C.); Architects